2020
DOI: 10.3389/fimmu.2020.577546
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Vaccination Elicits Cross-Reactive HLA-Class I-Restricted CD8 T Cell Response Against Zika Virus Infection

Abstract: Japanese encephalitis virus (JEV) exposure or vaccination could elicit cross-reactive CD8 T cell immunity against heterologous flaviviruses in humans. In addition, crossreactive CD8 T cells induced by dengue virus (DENV) have been shown to play a protective role against Zika virus (ZIKV). However, how JEV exposure or vaccination affects ZIKV infection in humans remains unclear. In this report, epitope prediction algorithms were used to predict the cross-reactive CD8 T cell epitope restricted to human HLA betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Cellular immunity played an important role in the cross-protective effect of prior JEV immunity on the sequential ZIKV infection [44,45]. In the JEV-vaccinated ifnar −/− adult mouse model, depletion of CD8 + T cells increased mortality, weight loss, and severity of clinical symptoms during ZIKV infection, indicating that CD8 + T cells were indispensable for the protective effect in the sequential infection of JEV-ZIKV [6].…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…Cellular immunity played an important role in the cross-protective effect of prior JEV immunity on the sequential ZIKV infection [44,45]. In the JEV-vaccinated ifnar −/− adult mouse model, depletion of CD8 + T cells increased mortality, weight loss, and severity of clinical symptoms during ZIKV infection, indicating that CD8 + T cells were indispensable for the protective effect in the sequential infection of JEV-ZIKV [6].…”
Section: The Impact Of Prior Jev Immunity On Zikv Infectionmentioning
confidence: 99%
“…184 Furthermore, JEV SA14-14-2 vaccine was found to provide cross-protection against ZIKV infection in mice and potential with low risk of ADE in immunecompetent humans. 186 In addition, there are no specific therapeutic drugs for dengue, and the treatment is only supportive care for severe dengue patients. Therefore, various forms of publicity and education should be carried out widely to popularize the knowledge of health emergencies contributes greatly to the control of dengue.…”
Section: Personal Protectionmentioning
confidence: 99%
“…Nevertheless, studies with different results have also been reported, such as anti‐JEV antibodies predisposed to symptomatic DF, 185 and the pre‐existing of JEV neutralizing antibodies increases the risk of DF by 2.75‐fold 184 . Furthermore, JEV SA14‐14‐2 vaccine was found to provide cross‐protection against ZIKV infection in mice and potential with low risk of ADE in immune‐competent humans 186 . In addition, there are no specific therapeutic drugs for dengue, and the treatment is only supportive care for severe dengue patients.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Thus, this vaccine may induce immunodominant responses toward non-structural proteins at the expense of structural antigens that have homology with those presented by the ZPIV vaccine. Our study also suggests that the presence of non-structural antigens or active virus replication may be needed to induce CD8 T cell responses, as robust CD8 T cell activation has been demonstrated upon ZIKV infection in human and mice studies ( 53 , 54 ), and cross-reactive CD8 T cell responses between a live attenuated JEV vaccine and ZIKV infection were described ( 55 ), but this type of response was not elicited by the ZPIV vaccine. The live-attenuated YFV vaccine is known to induce robust CD8 T cell responses ( 56 ).…”
Section: Discussionmentioning
confidence: 57%